Proportional representation electoral system and conflict management in divided societies: the case of Rwanda and Kenya - Akonumbo, Atangcho Nji (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr. Atangcho N Akonumbo, Faculté de Sciences Sociales et de Gestion, Université Catholique D’Afrique, Centrale Yaounde Cameroun.